Opening up new worlds for humans to respect - Dudding, Michael (Architectural History Aotearoa, 2022)
In 1967, New Zealand architect James Beard took a year-long professional sabbatical in the US to learn more about regional and landscape planning. Following personal advice from MIT’s Kevin Lynch, Beard headed to Harvard University to study toward a Master’s qualification in their highly regarded landscape department under Professor Hideo Sasaki. While Beard was able to employ some of his learning in his later career (most notably at Kaitoke Regional Park in the 1970s), Beard returned to a New Zealand that was not yet ready for the broader regional-level consideration of landscape planning and design that he had discovered in his US studies.